Disclosure and compliance of IAS 16 in DSE listed pharmaceuticals companies in Bangladesh - Al-Mumen, Sk. Abdullah (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.